Toxoplasmose como assunto de saúde pública na Sérvia - Djurković-Djaković, Olgica (Scientia Medica, 2010)
AIMS: To review the significance of toxoplasmosis as a public health issue in Serbia, and analyze the current strategies to alleviate the burden of the disease.SOURCE OF DATA: Relevant clinical and epidemiological reports from Serbia published since 1975.SUMMARY OF FINDINGS: Despite 50 years of continuous work on Toxoplasma gondii and toxoplasmosis in Serbia, exact data on the frequency of acute clinical disease, acute infections in pregnancy and congenital infection in the offspring are still lacking, due to the vague legal provision that toxoplasmosis is subject to reporting “in case of epidemiological indications”. What, however, is clear is that the major Toxoplasma-induced public health issue in Serbia, like elsewhere in Europe, is congenital toxoplasmosis. Continuous monitoring of particular patient groups showed a dramatic decrease in the prevalence of infection over the past two decades, and a consequently increased proportion of women susceptible to infection in pregnancy, suggesting a potential increase in the incidence of congenital toxoplasmosis. Studies of risk factors for infection transmission have provided data to guide national health education campaigns.CONCLUSIONS: It is expected that the recent appointment of the National Reference Laboratory for Toxoplasmosis as the focal point for the collection of data from the primary level, will provide the means for accurate assessment of the measure of the problem, which is a prerequisite of an evidence-based nation-wide prevention program. In the meantime, health education of all pregnant women, focused at risk factors of major local significance, is advocated as a sound and financially sustainable option to reduce congenital toxoplasmosis.